Productivity and soil fertility changes under continuous fertilization of rice (Oryza sativa) -rice cropping system - REDDY, M NAGESWARA; SITARAMAYYA, M; SWAMY, S NARAYANA; SRIRAM, A; KANTH, G KRISHNA (The Indian Journal of Agricultural Sciences, 2013)
A long-term experiment in an Udic Ustochrepts soil with rice (Oryza sativa L.) -rice cropping system was conducted during 1987-96 at Hyderabad to evaluate the effect of continuous cropping and fertilization on yield and soil fertility. Maximum doses of fertilizer @ N120 and P80 had increased grain yield by about 0.6 to 0.7 tonne more compared to N40 no P2 05 Potash application @ K40 kg/ha showed a meagre response. Net returns for the cropping system were maximum (Rs 13 180/ha) at N120 P8O K40’ Stability analysis of grain yield indicated that consistent productivity is possible with N80 P40 K0 both in rainy season (kharif) and winter season (rabi). After 10 consecutive years of cropping, available phosphorus and Potassium got depleted compared to their initial status. Available iron, zinc,pore space, water holding capacity and volume expansion showed increase over their initial values after 20 seasons of cropping. The trends clearly emphasised the need for balanced fertilization of rice for consistent productivity.